Electroencephalogram and physiological responses as affected by slaughter empathy in goats - Kumar, Pavan; Abubakar, Ahmed Abubakar; Ahmed, Muideen Adewale; Hayat, Muhammad Nizam; Ajat, Mokrish; Kaka, Ubedullah; Goh, Yong Meng; Sazili, Awis Qurni (Multidisciplinary Digital Publishing Institute, 2023)
Recent advances in emotions and cognitive science make it imperative to assess the emotional stress in goats at the time of slaughter. The present study was envisaged to study the electroencephalogram and physiological responses as affected by slaughter empathy in goats. A total of 12 goats were divided into two groups viz., E-group (goats exposed to slaughter environment, n = 6) and S-group (goat slaughtered in front of E-group, n = 6). The electroencephalogram and physiological responses in male Boer cross goats (E-group) were recorded in a slaughterhouse in two stages viz., control (C) without exposure to the slaughter of conspecifics and treatment (T) while visualizing the slaughter of conspecifics (S—slaughter group). The exposure of the goat to the slaughter of a conspecific resulted in a heightened emotional state. It caused significant alterations in neurobiological activity as recorded with the significant changes in the EEG spectrum (beta waves (p = 0.000491), theta waves (p = 0.017), and median frequency MF or F50 (p = 0.002)). Emotional stress was also observed to significantly increase blood glucose (p = 0.031) and a non-significant (p = 0.225) increase in heart rate in goats. Thus, slaughter empathy was observed to exert a significant effect on the electric activity of neurons in the cerebrocortical area of the brain and an increase in blood glucose content.